THE RELATIONSHIP BETWEEN SOCIAL RESPONSIBILITY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN 5 STARS HOTELS OPERATING IN PETRA CITY - Futa, Sahar Moh’d (European Scientific Journal, ESJ, 2013)
This study explored the degree to which 5 stars hotels operating in Petra city are considered socially responsible, and the linkage between social responsibility activities of these organizations and the citizenship behavior of employees. A sample of 80 out of 200 employees working at 2 five stars hotels, were surveyed. Four dimensions of social responsibility (the economic, ethical, philanthropic, and the legal) with 5 dimensions of citizenship behavior (Altruism, Curtsey, Sportsmanship, Civic Virtue and conscientiousness) were correlated, the results bring to light the positive association between the examined variables, the strongest relationship was with the legal dimension followed by philanthropic, then with the ethical, and the weakest relationship was with the economic dimension.